The ability of breadfruit starch nanoparticlestabilized pickering emulsion for encapsulating cinnamon essential oil - Harsanto, Bovi Wira; Supriyanto,; Indriana Kartini,; Pranoto, Yudi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cinnamon essential oil (CO) is susceptible to decreased stability during storage, limiting its application in food products. Pickering emulsion stabilized by starch nanoparticles becomes a potential encapsulating method that can improve CO stability. This study aimed to investigate the ability of breadfruit starch nanoparticles-stabilized Pickering emulsion to encapsulate CO with various concentrations. Encapsulation process was carried out using the high-energy emulsification method with dispersing CO (0.05%; 0.1%; 0.5%; 1% w/w) in emulsion. The loading efficiency of CO and emulsion properties were evaluated. Retention of CO was also observed in 7 days-storage. Results showed that 0.5% and 1% CO were encapsulated effectively and stable in Pickering emulsion, with loading efficiency and CO retention ranging from 79.49-81.13% and 78.86-79.20%, respectively. The addition of 0.5% and 1% CO increased yellowness (+a*: 7.45-8.99) as well as decreased whiteness (+L*: 85.77-86.06) and viscosity (629.9-721.8 cP) of Pickering emulsion. However, differences in CO concentrations did not affect the emulsion index of Pickering emulsion. These findings concluded that breadfruit starch nanoparticles-stabilized Pickering emulsion could encapsulate up to 0.5% and 1% CO with the best properties among other treatments. Therefore, breadfruit starch nanoparticlesstabilized Pickering emulsion can be an alternative as encapsulation method, which can later expand the application of CO in food products.